Enhancing therapeutic potential of poor aqueous soluble herbal drugs through solid dispersion-An overview - Shahid Ud Din Wani; Vasundhra Kakkar; Surya Prakash Gautam; Gangadharappa HV; Mohammad Ali; Mubashir Hussain Masoodi; Afrasim Moin (Elsevier, 2021)
Background: Poorly water-soluble medicaments continue to be a challenging, however, significant class of herbal drugs for the management of an extensive range of ailments. Solid dispersion (SD) has emerged as one of the most effective formulation approaches to enhance the dissolution of poorly water-soluble herbal drugs. Formulation of solid dispersion is one of the most effective methods to enhance the aqueous solubility of highly lipophilic drugs which belong to BCS class II and IV. An amorphous form of the drug is more unstable and highly soluble in water and is attained by formulating solid dispersion. Purpose: This review explains various physicochemical properties, criteria for carrier selection, and causes of instability of solid dispersion to improve the therapeutic potential of poorly water-soluble herbal drugs. Methodology: To classify and explain some newer techniques used nowadays along with solid dispersion which could prevent recrystallization and precipitation of drug. Some herbal drugs with high therapeutic value and poor aqueous solubility were also enlisted which could be formulated in the form of solid dispersion to have better oral bioavailability. Results: The solid dispersions studies have revealed better performance for the dissolution which might be due to its alteration from crystalline to amorphous form in addition to the adherence of hydrophilic carriers to the surface of poorly water-soluble herbal drugs. These techniques will assist in the formation of a more stable solid dispersion. Conclusion: The application of solid dispersion technique in enhancing the aqueous solubility of poorly aqueous soluble herbal drugs should direct to the constant and enhanced bioavailability, leading to an enhanced therapeutic potential.